A simple separation system for elimination of molecular interferences for purity determination of europium and ytterbium oxides by HPLC-ICP-MS. Issue 11 (14th September 2020) - Nguyen, Viet Hung; Ramzan, Muhammad; Kifle, Dejene; Wibetoe, Grethe
Abstract : A simple and rapid HPLC-ICP-MS method for determination of ultra-trace REE impurities in highly pure Eu2 O3 and Yb2 O3 has been developed. Abstract : A simple and rapid HPLC-ICP-MS method for determination of ultra-trace REE impurities in highly pure Eu2 O3 and Yb2 O3 has been developed. The majority of REEs as trace impurities in both Eu2 O3 and Yb2 O3 matrices can be determined solely by ICP-MS. However, 153 Eu 16 O + and 174 YbH + formed in the plasma of the ICP-MS overlap with the monoisotopic 169 Tm + and the most abundant isotope of Lu ( 175 Lu + ), respectively. Spectral interferences caused by the formation of matrix-based polyatomic ions are eliminated by separating the highly concentrated matrix element from the spectrally interfering elements of interest. This is achieved by coupling HPLC to ICP-MS. A reversed-phase C-18-silica HPLC column impregnated with 2-ethylhexyl, 2-ethylhexyl phosphonic acid (H[EH(EHP)]) is prepared and used as a separation tool. The method allows separation of problematic REEs, viz Eu from Tm and Yb from Lu in time and space prior to entering the ICP-MS, which enables accurate determination of the REEs in question. The method is used to characterize high purity Eu2 O3 and Yb2 O3 through the impurity approach, focusing on trace concentrations of other REEs in the respective oxides. The method is rapid with a separation time of 3.5 minutes, which makes it suitable for routine analysis of trace levels of all REE impurities, including Tm and Lu in high-purity europium and ytterbium oxides. The chromatographic system is compatible with ICP-MS as the mobile phase consists only of diluted HNO3 .